Estudio comparativo del diseño geométrico de carretera con levantamiento topográfico (estación total, modelo digital Google-earth), en la provincia de Angaraes - Surichaqui, Franklin (2023)
The present research work called "Comparative study of the geometric design of a road, using topographic survey (total station and google earth digital model), in the province of Angaraes - Huancavelica" studies a section of approximately 1 + 500 km, which corresponds to the Piscopampa - Latapuquio highway. The development process corresponds to the type of descriptive - comparative research, for which the methods of topographic survey with total station and the technique of the Google Earth digital model are used, with the purpose of preparing the comparative study of the geometric design of the Piscopampa highway. - Latapuquio, using the topographic survey with a total station and the Google Earth digital model. It should be noted that georeferencing activities of the study area were carried out with a GPS support point and a geodesic point authorized by the IGN, which is located on the roof of the premises of the Provincial Municipality of Angaraes, for this reason there has been a compilation of UTM data by the traditional method of topographic survey and obtaining UTM data through the Google Earth digital model. therefore: The Google Earth digital model with 95% versatility stands out in reference to speed and optimization of time, however, it does not meet the conditions of throwing earthwork volumes, the positional accuracy of UTM data, while with the topographic survey, the UTM data is obtained accurately and guarantees to obtain the earthworks (cut and fill).